2002
DOI: 10.1002/rcm.832
|View full text |Cite
|
Sign up to set email alerts
|

On‐line microdialysis for enhanced resolution and sensitivity during electrospray mass spectrometry of non‐covalent complexes and competitive binding studies

Abstract: Many proteins and macromolecules easily form metal adduct ions which impairs their analysis by mass spectrometry. The present study describes how the formation of undesired adducts can be minimized by on-line microdialysis for non-covalent binding studies of macromolecules with low molecular mass ligands with electrospray ionization mass spectrometry (ESI-MS). The technique was indispensable for protein-ligand studies due to reduction of unwanted adduct ions, and thus gave excellent resolution and a sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…20,30 Other larger molecules may also bind to a target molecule in a nonspecific manner. Jorgensen et al 31 recently showed nonspecific interactions between peptides and vancomycin.…”
Section: Nonspecific Versus Specific Protein-ligand Interactionmentioning
confidence: 99%
“…20,30 Other larger molecules may also bind to a target molecule in a nonspecific manner. Jorgensen et al 31 recently showed nonspecific interactions between peptides and vancomycin.…”
Section: Nonspecific Versus Specific Protein-ligand Interactionmentioning
confidence: 99%
“…Many proteins and macromolecules rapidly form metal adduct ions when analyzed in pure buffer solutions, which impairs their analysis by mass spectrometry. Unwanted adduct formation can be reduced by using microdialysis 15 or an in-line size-exclusion chromatography gel filtration cartridge. 16 Second, hydrophobic interactions are weaker in the gas phase than the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…A few existing designs employ such injectors, with the smallest sample volumes of 5 to 6 µl reported. 7,16,27 Lutz et al used a similar microinjector, although their method included a sheath flow rate of 5 µl/min with a standard ESI source. 7 In comparison, we utilize an ESI-friendly solvent to carry the plug of injected sample and an NSI source, as discussed in the following section.…”
Section: Microdialysis Unit Designmentioning
confidence: 98%